The Spotify Effect: Digital Distribution and Financial Growth - Vonderau, Patrick (Television & New Media, 2019)
This article analyzes Spotify as a media company that operates at the intersection of advertising, technology, music, and finance. In doing so, this article contributes to media industry studies as a field that investigates the relation between various industrial and economic actors. Given that the media industries, as any other industry, can be defined as a set of markets, one of which is the leading market, and to which other markets are auxiliary, the question asked is what market is leading in the case of Spotify. What the article describes as the “Spotify effect” is the company’s ability to fold markets into each other: to make disappear an aggressive financial growth strategy and business set-up based on ad tech engineering by creating an aura of Nordic cool and public benefit around its use of music. Spotify’s financial strategy has implications for the digital distribution of cultural content more generally.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNTI3NDc2NDE3NzQxMjAw